CAUSAL OR EFFECTUAL? AN EXPLORATORY STUDY ON WOMEN’S ENTREPRENEURIAL BEHAVIOR AND DECISION-MAKING LOGIC - Annie Banikema; Thrycia Tite (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2018)
Basing on the principle of causation vs effectuation, we try in this research to undersantand women’s entrepreneurial process and their decision-making logic in the process of entrepreneurial action. Specifically, we seek (1) to understand under what conditions female entrepreneurs mobilize effectual rationality or causal rationality to make decisions and act and (2) to explain the preference for causal or effectual behavior among female entrepreneurs. Research method includes a qualitative approach, through In-depth and semi-structured interviews. Those were conducted with 10 female entrepreneurs, at different stage of their entrepreneurial process, and analyzed through a content analysis. Consistent with existing literature, our results highlight variables that can potentially influence the use of effectual or causal logic: Entrepreneurial expertise and entrepreneurial uncertainty. More interesting this research points out the link between entrepreneurial mo-tivations and the type of decision-making logic used by female entrepreneurs